Якість як принципова вимога дієвого закону - Мельник, А.А. (Альманах права, 2012)
У статті здійснюється аналіз категорії якість закону через осмислення філософського та філологічного її значення. Визначаються показники якості закону в їх співвідношенні з його властивостям. Досліджено критерії якості закону, його складові та фактори, що визначають якість як вимогу діючого закону. В статье проводиться анализ категорий качества закона через осмысление философского и филологического его значения. Определяются показатели качества в их соотношении с его свойствами. Исследовано критерии качества закона и факторы, которые определяют качество как требование действующего закона. This article provides analysis of the quality of law through the understanding of its philosophical and philological sense. Comparison of various ways of understanding and interpretation of the term «quality» is provided in order to define its clear meaning. Law quality criteria are determined in accordance with their properties. There are several levels of understanding the essence of quality. According to Aristotel, who was one of the first to give a certain definition of «quality», the quality is the essence that helps any object or process to obtain certain features, which may be judged as a quality features under specific conditions. In literature it is often defined that quality has its inner core, which describes the quality as a basic form of effectiveness and does not depend on human evaluations. The secondary (outer) core is based on human views that are often subjective. Subjective view on the quality itself is a powerful tool of creating laws and adopting them to a specific country, nation or social group. Philological definition of laws is not less important. For instance in Ukrainian philology term «quality» is defined as a number of criteria and features of an object, which make it unique and unlike others, make it more valuable or useful for specific uses. Philosophical interpretation of the term «quality» is based on the understanding that only the sum of relative criteria and specifications may be the basement of understanding real quality features of any object or process. According to philosophical view on the quality of law, the level of law effectiveness may be determined by law quality features. In this article, law quality criteria were examined, as well as components and elements which identify the quality as the main requirement of current law. The identification of the basic quality criteria of law is the basis of setting standards of law quality. Worldwide practice of implementation of law quality standards shows the importance of effectiveness or current laws. These international standards can be seen in international law documents, agreements, international conventions, the spread of which is not limited by a single country, nation or even continent. Due to the international coverage, it is vital for those laws to be designed with the highest standards of effectiveness. Standards of law effectiveness may be defined as a complicated system of template ways of building laws, which contains most valuable components that may be implemented in the process of creating laws. Components used in the process should have contemporary nature and moreover they have to reflect the current social issues, together with the perspectives of social relations development.